A new Siphonoperla species from the Eastern Alps (Plecoptera: Chloroperlidae), with comments on the genus - Graf, Wolfram; Stradner, Dennis; Weiss, Steve (Zootaxa, 2008)
We describe a new species of stonefly from the genus Siphonoperla, from a glacial refuge in the Eastern Alps of Austria. The species’ unique genitalia among congenitors as well as high genetic divergence from the co-occuring Siphonoperla montana strongly support its status as a distinct species. We describe Siphonoperla ottomoogi nov. sp. based on morphological and genetic characteristics as well as provide notes on its presumed habitat and distribution. Further notes on the biogeography of the genus are provided.